2017
DOI: 10.1016/j.yjmcc.2017.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial specific SIRT3 deletion impairs glycolysis and angiogenesis and causes diastolic dysfunction

Abstract: Endothelial glycolysis plays a critical role in the regulation of angiogenesis. We investigated the role of Sirtuin 3 (SIRT3) on endothelial cell (EC) glycolytic metabolism, angiogenesis, and diastolic function. Our aim was to test the hypothesis that loss of SIRT3 in ECs impairs endothelial glycolytic metabolism and angiogenesis and contributes to myocardial capillary rarefaction and the development of diastolic dysfunction. Using SIRT3 deficient ECs, SIRT3 was found to regulate a metabolic switch between mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
103
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 88 publications
(110 citation statements)
references
References 44 publications
7
103
0
Order By: Relevance
“…Consistent with these clinical observation, our study revealed that global SIRT3 KO mice develop coronary microvascular dysfunction and diastolic dysfunction, associated with decreased myocardial capillary density and pericyte coverage (He et al, ). Similarly, endothelial‐specific SIRT3 knockout (ECKO) mice also exhibit decreased coronary function and diastolic function (He et al, ). These studies indicate that endothelial function plays an important role in cardiac homeostasis involving SIRT3‐mediated cellular function.…”
Section: Sirt3 In Cardiac Function and Cardiovascular Diseasementioning
confidence: 99%
“…Consistent with these clinical observation, our study revealed that global SIRT3 KO mice develop coronary microvascular dysfunction and diastolic dysfunction, associated with decreased myocardial capillary density and pericyte coverage (He et al, ). Similarly, endothelial‐specific SIRT3 knockout (ECKO) mice also exhibit decreased coronary function and diastolic function (He et al, ). These studies indicate that endothelial function plays an important role in cardiac homeostasis involving SIRT3‐mediated cellular function.…”
Section: Sirt3 In Cardiac Function and Cardiovascular Diseasementioning
confidence: 99%
“…Therefore, increased Ang-2 and TGF-β in the liver tissues may be responsible for hepatic fibrosis in the PHD2 EC KO mice. In addition, inhibition of PFKFB3 has been shown to increase Ang-2 expression in the EC [37]. Treatment with ANP has been shown to reduce liver fibrosis [38].…”
Section: Discussionmentioning
confidence: 99%
“…Cellular bioenergetics was measured using a Seahorse XFe24 extracellular flux analyzer in intact cardiomyocytes. We conducted glycolysis stress testing following the manufacturer's instructions as previously reported [ 25 ]. Glycolysis stress test: cells were incubated in glucose-free Seahorse assay media supplemented with 1 mM pyruvate at 37°C in an incubator without CO 2 for 1 h prior to the assay.…”
Section: Methodsmentioning
confidence: 99%